2008
DOI: 10.1002/0471143030.cb0419s39
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Colocalization Analysis of Confocal Fluorescence Microscopy Images

Abstract: Colocalization is an important finding in many cell biological studies. This unit describes a protocol for quantitative evaluation of images with colocalization based on the calculation of a number of specialized coefficients. First, images of double‐stained sections are subjected to background correction. Then, various coefficients are calculated. Meanings of the coefficients and a guide to interpretation of their results indicating either presence or absence of colocalization are given. Success in colocaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
148
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(156 citation statements)
references
References 26 publications
(27 reference statements)
5
148
0
Order By: Relevance
“…The untagged M26R GCAP1 displaced GCAP1-GFP in the same manner (Fig. 3D), causing PCC to fall to 0.32 Ϯ 0.16 (n ϭ 36), which is below the co-localization threshold (51). Hence, the M26R GCAP1 eliminated RetGC1 activation in Fig.…”
Section: Gcap1 and Gcap2 Compete For Binding To The Same Retgc1mentioning
confidence: 70%
“…The untagged M26R GCAP1 displaced GCAP1-GFP in the same manner (Fig. 3D), causing PCC to fall to 0.32 Ϯ 0.16 (n ϭ 36), which is below the co-localization threshold (51). Hence, the M26R GCAP1 eliminated RetGC1 activation in Fig.…”
Section: Gcap1 and Gcap2 Compete For Binding To The Same Retgc1mentioning
confidence: 70%
“…Similar experiments were performed in N2a cells after control or synj1 siRNA transfection, followed by incubation with Alexa-A␤ 555 or Alexa-A␤ 488 . Fluorescent colocalization analysis was quantified using the Zen program to calculate colocalized pixels (subtracted by background) and colocalization coefficiency as previously described (30,31). The data are presented as percentages of control Ϯ S.E.…”
Section: Methodsmentioning
confidence: 99%
“…It turns out that the most commonly used parameter, the so-called Pearson's Correlation Coefficient (PCC) is superior to the Manders Overlap Coefficient [13,14] (MOC) which is currently implemented in most commercial software packages for image processing [15]. A closer look at the PCC, however, reveals that it has some frequently cited major drawbacks which significantly limit its utility for colocalization analysis in certain cases [16][17][18][19][20]. For example, it was found that the PCC, which can adopt values between þ1 and À1 as a measure of the similarity of channels (+1: perfect colocalization; values between 0 and À1: no colocalization), is very sensitive to strong intensity fluctuations or threshold variations.…”
Section: Biophotonicsmentioning
confidence: 99%